Conditions for the implementation of the Union support under the Common Agricultural Policy for 2028–2034 - Czechowski, Paweł; Niewiadomski, Adam (Przegląd Prawa Rolnego, 2025)
This analysis aims to provide a preliminary evaluation of the proposal for a regulation of the European Parliament and of the Council establishing the conditions for the implementation of the Union support to the Common Agricultural Policy for the period from 2028 to 2034. Both, the rationale behind the legislative proposal and the wording of the draft provisions have been taken into account. When formulating this evaluation, the authors considered the experience gained in implementing the CAP during the current financing period, the challenges facing the European agricultural sector, and the European Commission’s vision for the future of this sector, as set out in the communication “A Vision for Agriculture and Food” to the European Parliament, the Council, the European Economic and Social Committee, and the Committee of the Regions. This document does not clearly align with the provisions of trade agreements. Further simplification of agricultural policy in the European Union is also needed. Concluding, the submitted proposal introduces many new solutions but also entails new requirements for beneficiaries.